(untitled) (Bangladesh Journal of Anatomy, 2013)
Context: There is a variation in the arrangement of structures at hilum which may create problem for the surgeon during dissection of hilum of kidney. Moreover, developmental anomalies like, constriction at pelviureteric region, double renal pelvis, accessory renal arteries etc are not uncommon. So, adequate anatomical knowledge of kidney specially at hilum is required for successful surgery of this reason. Objective: To study the variation in the arrangement of renal vessels and renal pelvis at hilum. Study design: Descriptive type. Place and period: Department of Anatomy, Mymensingh Medical College, Mymensingh, Bangladesh from January 2004 to June 2005. Materials and methods: A total of 100 fresh human kidneys of both sexes and sides were collected from the morgue of Mymensingh Medical College at postmortem. The selected cases were between 5 to 60 years of age. The samples were preserved to observe the variations in the arrangement of main structures at hilum of kidneys regardless of age groups. Results: When hilum of the kidneys viewed before backwards, anteriorly and at the middle, there was 1% variation in the arrangement of renal vessels but posteriorly renal pelvis was found in variably and it was double in 2% of kidneys. Posterior division of renal artery was present behind the renal pelvis in 12% of kidneys. Conclusion: Variation in the arrangement of structures at hilum was observed in 1% of kidneys. DOI: http://dx.doi.org/10.3329/bja.v10i2.17322 Bangladesh Journal of Anatomy, July 2012, Vol. 10 No. 2 pp 76-79